Analisis Sistem Pemasaran Bubuk Kopi Sidikalang - Riki Andika Sinamo; Marizha Nurcahyani (Universitas Medan Area, 2026)
Dairi Regency, especially Sidikalang, is known as one of the best coffee-producing areas in Indonesia. This study aims to analyze Sidikalang's coffee powder marketing system, including distribution channels, marketing costs, profit margins, and marketing efficiency at various levels of the distribution chain. The research method used is quantitative descriptive analysis with a survey approach to farmers, coffee powder producers, and intermediary traders. The results of the study show that there are three main channels of marketing Sidikalang coffee powder, with significant differences in terms of profit margin and marketing efficiency.